Wildlife roadkill involving native mammals in Peninsular Malaysia - Sukami, Mohd Edinoor Anuar (2016)
In Peninsular Malaysia, wildlife roadkill is a minor case and rarely happen. However, it can become a serious threat with the occurrence of wildlife habitat fragmentation. This study will help to view on the effect of wildlife roadkill involving native mammals in Peninsular Malaysia. Two main objectives of this study were to assess the effect of roadkill to the two types of roads which have been classified as plantation road and non-plantation road. The second objective was to compare the number of mammals killed according to the three categories of mammals which are big-sized mammals, medium-sized mammals and large-sized mammals. This study is based on the wildlife roadkill database collected by Department of Wildlife and National Park (DWNP) Peninsular Malaysia starting from the year of 2010 to 2014. Throughout the period, it was reported that total 605 killed of mammals resulting from roadkill. Out of that figure, 159 (26%) were recorded killed in plantation road while 449 (74%) were killed at non-plantation road. The result shows that the total number of mammals found killed on plantation road (mean ± standard error = 1.926 ± 0.03755) is significantly higher than (f-value = 67.01; p-value < 0.001) on the non-plantation road (mean ± standard error = 1.111 ± 0.01551). Result comparison between three type of mammals shows that the mean value for medium-sized mammals is 0.815 with a range of (0,8587, 0,9471), followed by big-sized mammals with a mean value of 0.047 with a range of (0,1735, 0,2619) and the least is the small-sized mammals with a mean value of 0.0002 with a range of (-,0310, 0,0574). The confidence interval used is at 95%. Based on the current situation of the surrounding habitat, wildlife population in Peninsular Malaysia and previous research conducted in other countries, it was found that the main reason that causes mammalian wildlife roadkill is because of habitat fragmentation. Habitat fragmentation involves the change of land use from the forested area to development and plantation area. Because of that, the mammals home range and their territory are disrupted and become limited. The existence of a high population of medium-sized mammals in Peninsular Malaysia is the main factor which causes the number of roadkill for this category to be the highest among the three categories. Overall, the type of roads is able to influence the rate of wildlife mammals roadkill. The aspect of road infrastructure facilities should be improved in order to reduce cases of wildlife mammals roadkill in Peninsular Malaysia.